Online Health Information Seeking: A Review and Meta-Analysis - Wang, Xiaohui; Shi, Jingyuan; Kong, Hanxiao (Health communication, 2021)
Online health information, as an emerging field in health communication research, has attracted close attention from researchers. To identify major determinants of why individuals seek health information online, we conducted a meta-analysis that systematically accumulates the existing research findings. To that end, by integrating three theories or models for examining information-seeking behavior, we developed a theoretical framework for the current meta-analysis that emphasizing psychosocial, instrumental, contextual, and demographic factors. By analyzing the effect sizes from 44 articles representing 54 empirical samples, we found that the quality, trustworthiness, and utility of online health information were the dominant predictors of seeking it and that instrumental factors were more important than psychological ones in determining whether individuals did so. Moreover, the development of information and communication technology, the sampling method, and the type of information sought significantly moderated pairwise relationships between determinants and seeking behavior, whereas culture did not. Herein, we discuss the theoretical implications of our findings as well as directions for future research.